117k views
1 vote
**The function f(x) = (x - 7)^2 - 3 istransformed into the function h(x)=a(x- 7)^2 - 3 (shown below). What is thevalue of a?

**The function f(x) = (x - 7)^2 - 3 istransformed into the function h(x)=a(x- 7)^2 - 3 (shown-example-1
User Shaun Ryan
by
5.5k points

1 Answer

3 votes

Answer:


\begin{gathered} a=(1)/(7) \\ h(x)=(1)/(7)(x-7)^2-3 \end{gathered}

Explanation:

We know that the ''a'' coefficient represents a stretch or compression, if it is between 0 and 1, it is a horizontal stretch:


\begin{gathered} h(x)=a(x-7)^2-3 \\ \text{ Since we know that at x=0, h(x)=4} \\ 4=a(0-7)^2-3 \\ 4=49a-3 \\ 49a=7 \\ a=(7)/(49) \\ a=(1)/(7) \end{gathered}

Therefore, the equation for the function shown is:


h(x)=(1)/(7)(x-7)^2-3

User Plodder
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.